(untitled) (Innovative professional education, 2024)
This study explores the differences between the terms "online educational platform" and "electronic educational platform," emphasizing their interconnections and distinctions within the context of contemporary education. By analyzing various aspects of both platforms, their impact on the learning process is highlighted. Special attention is given to the importance of evaluation factors for digital educational platforms. The possibilities for optimizing the learning environment to meet the needs of modern society are identified.